Factors Associated with Utilization of Antenatal Care Services among Women in Noakhali District, Bangladesh - Shill, Lincon Chandra; Tithi, Shawon Hasan; Jahan, Israt; Mokbul, Mansura; Saha, Priya; Alam, Syeda Saima (International Journal of Child Health and Nutrition, 2024)
A cross-sectional study sought to uncover the determinants affecting antenatal care (ANC) utilization among pregnant women in Noakhali District, Bangladesh. Data from 400 women were gathered utilizing a standardized questionnaire, and the analysis was performed using SPSS software (version 23.0), incorporating descriptive statistics, Chi-square tests, and multinomial logistic regression. The research revealed that merely 47.8% of individuals attended a minimum of four antenatal care visits, as advised by healthcare recommendations. The frequency of ANC visits was substantially correlated with socioeconomic status, educational attainment, work status, and obstacles to receiving ANC services. Mothers with 1-3 antenatal care visits encountered 26.58 times more barriers to attending visits than those who completed four or more visits (OR: 26.58, 95% CI: 11.28-62.62). Moreover, income levels were 0.53 times greater among mothers with fewer antenatal care appointments in comparison to those with four visits (OR: 0.53, 95% CI: 0.32-0.86). The report emphasizes the need to address the constraints preventing women from getting enough ANC. This necessitates enhancements in transportation, the quality of healthcare facilities, and the training and accessibility of healthcare staff. Enhancing awareness of the significance of ANC through focused campaigns is essential at the local, national, and worldwide levels. Addressing these challenges is crucial for enhancing ANC utilization and promising improved maternal and newborn health outcomes in the region.